Recovery in the soil‑plant system of nitrogen from green manure applied on cabbage crop - Araújo, Ednaldo da Silva; Guerra, José Guilherme Marinho; Espindola, José Antônio Azevedo; Urquiaga, Segundo; Boddey, Robert Michael; Martelleto, Luiz Aurélio Peres; Alves, Bruno José Rodrigues (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to determine, in the soil‑plant system, the recovery efficiency of N derived from green manure applied on cabbage (Brassica oleracea) crop. The experiment was divided into two stages: the first one consisted of the straw production of jack bean (Canavalia ensiformis), velvet bean (Mucuna cinereum), and sorghum (Sorghum bicolor), in substrate enriched with 15N. The second stage consisted of the application of 15N-labeled green manure on the cabbage beds. Treatments consisted of: fresh residues of jack bean; fresh residues of velvet bean; fresh residues of sorghum; mixture of residues of jack bean, velvet bean, and sorghum at 1:1:1; and control without green manure addition. The N recovery in the soil–plant system was influenced by the green manure species used, and the recovery efficiency of the N derived from the green manure legumes varied from 9 to 16%. The jack bean treatment shows a greater recovery efficiency of nitrogen and, therefore, the best synchrony of N supply, by straw decomposition, with the cabbage crop demand.